ANALISIS KESALAHAN MENULIS KATA BAKU PADA PELAJARAN BAHASA INDONESIA KELAS 4 SD - Rakhmah, Ana Afifatur; Purnomo , Heru (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
This descriptive qualitative research aims to analyze students’ errors in using standard and non-standard words in written texts. The study involved fourth-grade elementary students as subjects, whose writing results were analyzed using content analysis techniques. The findings showed that students frequently used non-standard words due to a lack of vocabulary mastery, exposure to informal language in daily life, and insufficient correction during the learning process. Common errors included the use of colloquial expressions, incorrect affixes, and informal spelling. The results highlight the need for improved learning strategies that emphasize vocabulary enrichment and structured practice in using standard language in written form.